Penerapan Metode Bernyanyi Dengan Gambar Untuk Meningkatkan Kemampuan Mengenal Lambang Bilangan Anak Usia 5-6 Tahun di Tk Boanerges Kids Kima Atas - Fera Luicia Tampi (Peneliti.net, 2022)
This research was conducted with the aim of describing the visual ability to recognize number symbols in children aged 5-6 years at Boanergese Kids Kindergarten in Kima Atas Village, through the method of singing with pictures. Referring to the nature of the problem and research objectives, it seems that the research is of a qualitative nature, so that the relevant methods used are qualitative and naturalistic methods. This research is planned to spend 6 months and be carried out in the Boanergese Kids Kindergarten, Kima Atas Village. The data collected in this study is qualitative data, namely in the form of information expressions in the form of words and sentences, events or activities of research subjects, and data in written form available in documents. Data collection techniques that will be used in this study are observation, interviews, and documentation studies. The data analysis technique used in this research is descriptive qualitative analysis. The data analysis process in this study uses the Miles model interactive analysis process, namely data reduction, data collection, data presentation, and drawing conclusions. Based on the observations from this study, children will be very interested in participating in learning in an effort to be able to recognize number symbols through singing with fun pictures and can stimulate children to be more active and focus on the learning process. This shows that playing while learning is a principle in learning in kindergarten (TK) and PAUD in general. It can be seen in this study that based on observation, ongoing learning and interviews, there are very well developed criteria with an average presentation of 72.66%. Based on the results of the research and discussion, it was concluded that the application of the singing method with pictures can improve the ability to recognize number symbols for children aged 5-6 years in Boanergese Kids Kindergarten.